PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERUSAHAAN - Rosa Fitriana; Husaeri Priatna; Djodi Setiawan; Titin Sulastri (ITB AAS INDONESIA, 2022)
This study aims to determine the effect of disclosure of corporate social responsibility and good corporate governance on the company's financial performance at PT Perkebunan Nusantara VIII. This study uses a quantitative approach using descriptive and verification research methods that describe the analysis of a result, then tests the hypothesis from the data and facts. The data used in this study is time series and the data source used is secondary data. The data analysis methods used are classical assumption test, multiple linear regression analysis, Pearson correlation coefficient test, partial correlation coefficient, coefficient of determination, and hypothesis testing using t-test and F-test. The population in this study is the financial statements and GCG indicators of PT Perkebunan Nusantara VIII. Then adjusted to the criteria that have been set. The sampling method is done by purposive sampling technique. Based on the research that has been done that there is a significant influence on the disclosure of corporate social responsibility and good corporate governance on the financial performance of PT. Perkebunan Nusantara VIII.